Hardware Implementation of Solar Photovoltaic System based Half Bridge Series Parallel Resonant Converter for Battery Charger - Rakhi K; Ilango Karuppasamy; Manjula G Nair (Institute of Advanced Engineering and Science, 2017)
The long established battery chargers are having many drawbacks such as prominent ripple charging current, less efficiency and bulky in size. To overcome these drawbacks of conventional battery charger, several charging circuits have been proposed and inevitability force to design a high-performance battery charger with small in size and improved efficiency. In this paper solar photovoltaic system based half-bridge series–parallel resonant converter (HBSPRC) charger is proposed for battery interface. The converter is designed to abolish low and high-frequency ripple currents and thus take full advantage of the life of secondary battery circuit. This is achieved by designing converter switches turn on at zero current and zero voltage with switching frequency greater than that of resonance frequency which leads to freewheeling diodes need not have very fast reverse-recovery characteristics. The performance of the power converters depends upon the control method adopted; in this work fuzzy logic controller is used for controlling the output voltage of HBSPRC. The fuzzy control scheme for the HBSPR converter has been designed and validated in hardware implementation of HBSPRC switching technique. From the results, it is found that the proposed battery charging system which reduces the switching loss and voltage stress across the power switches which increases the efficiency of the converter.